High-Pressure, High-Paying Jobs? - Markus Nagler; Johannes Rincke; Erwin Winkler (Center for Economic Studies and ifo Institute (CESifo), 2022)
Work-related stress has reportedly increased over time. Using worker-level survey data, we build a measure of work pressure strongly associated with adverse health outcomes. In line with theories of compensating differentials, work pressure comes with a sizable earnings premium, even within narrowly defined occupations. As expected, we find no premium among civil servants who face strong labor market frictions. In complementary stated-choice experiments, we uncover a substantial willingness-to-pay to avoid work pressure. Our evidence is consistent with workers sorting into high- and low-pressure jobs. Differences in the prevalence and valuation of work pressure explain a substantial share of wage inequality.
Keywords: I10; I31; J20; J31; J32; J81; M52; 330; work pressure; compensating differentials; working conditions; wage inequality; health